2022
DOI: 10.1055/s-0041-1740947
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19-Related Acute Invasive Fungal Sinusitis: Clinical Features and Outcomes

Abstract: Introduction There is a noticeable increase in the incidence of acute invasive fungal sinusitis which coincides with the ongoing coronavirus pandemic. It is a potentially-lethal fungal infection, with the most common form being the rhino-orbito-cerebral presentation. Objectives The aim of the present study is to discuss the different epidemiological factors, risk factors, clinical presentations and outcomes of acute invasive fungal sinusitis which is noticeably related to the coronavirus disease 2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…8 Invasive fungal sinusitis has also been shown to be more common in immunecompromised patients, such as those with diabetic, renal, and liver dysfunction. 5,9,10 Interestingly, there have been articles published on IFS in patients who recovered from COVID-19. On multivariate analysis, a history of COVID-19 infection was an independent risk factor when controlling for other comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Invasive fungal sinusitis has also been shown to be more common in immunecompromised patients, such as those with diabetic, renal, and liver dysfunction. 5,9,10 Interestingly, there have been articles published on IFS in patients who recovered from COVID-19. On multivariate analysis, a history of COVID-19 infection was an independent risk factor when controlling for other comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Invasive fungal sinusitis has also been shown to be more common in immune-compromised patients, such as those with diabetic, renal, and liver dysfunction. 5 , 9 , 10 …”
Section: Discussionmentioning
confidence: 99%
“…According to the pathological results, mucormycosis was confirmed in 19 patients (86.4%) and aspergillus in only 3 patients (13.6%). The treatment outcome included total improvement in 10 patients (45.5%), intracranial extension in 10 patents (45.5%), and 6 patients died from the disease (the mortality rate was 27.3%) [ 37 ]. Dilek et al systematically reviewed COVID-19-associated mucormycosis in 100 patients.…”
Section: Reviewmentioning
confidence: 99%
“…To date, there have been many reports on the association between acute invasive fungal rhinosinusitis and COVID-19 infection [ 37 , 38 , 39 , 40 ]. Abdelsamie et al presented a cross-sectional cohort study of 22 adult COVID-19 patients with concomitantly confirmed acute invasive fungal rhinosinusitis.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation